2019
DOI: 10.1159/000504219
|View full text |Cite
|
Sign up to set email alerts
|

Taller-Than-Wide Shape: A New Definition Improves the Specificity of TIRADS Systems

Abstract: Introduction: A taller-than-wide (TTW) shape is a suspicious feature of thyroid nodules commonly defined as an anteroposterior/transverse diameter (AP/T) ratio >1. An intraobserver variability of up to 18% in AP diameter evaluations has been described, which may lead to overreporting of this feature. To potentially improve the reliability of the TTW definition, we propose an arbitrary ratio of ≥1.2. Objective: The aim of this study was to estimate the impact of this definition on diagnostic performance. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…Likewise, Kim reported that a taller than wide shape did not contribute to an increased risk of malignant PCTNs. The reason may lie in the noted inter- and even intraobserver variability of taller-than-wide shape ( 30 , 31 ). Hypoechogenicity showed fair diagnostic performance in our review (AUC = 0.8092).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Kim reported that a taller than wide shape did not contribute to an increased risk of malignant PCTNs. The reason may lie in the noted inter- and even intraobserver variability of taller-than-wide shape ( 30 , 31 ). Hypoechogenicity showed fair diagnostic performance in our review (AUC = 0.8092).…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, the European Thyroid Association ( 14 ), the Korean Society of Thyroid Radiology ( 15 ), and the ACR ( 32 ) have developed specific lexicons to be used with their risk-assessment systems. The definitions of certain critical nodule descriptors, such as echogenicity ( 33 ), shape ( 34 ), hyperechoic foci ( 35 ), and extrathyroidal extension ( 36 ), can significantly impact the diagnostic performance of thyroid US. As a result, interobserver agreement for US-based risk-stratification systems remains only fair to moderate (kappa, 0.34-0.44) ( 10 ).…”
Section: Thyroid Ultrasound and Sonographic Risk-stratification Systementioning
confidence: 99%
“…The TIRADS lexicon is based on internal components (solid, mixed or cystic), echogenicity (hyper-, iso-, hypoechoic or markedly hypoechoic), margins (regular, microlobulated; irregular/spiculated), the presence of calcifications (micro or macro), and shape (taller-thanwide shape is recorded when the anteroposterior diameter is greater than the transverse one [28]; wider-than-tall shape in cases where the opposite is true) at ultrasound evaluation.…”
Section: Tirads Lexiconmentioning
confidence: 99%